Ionophoretic Study on Complexation of Manganese(II), Iron(II), Cobalt(II) and nickel(II) with m-Chloro-bezoic acid and Nitrilo-triacetic Acid - Pandey, R.S.; Pandey, C.S. (Asian Journal of Chemistry, 2010)
Paper-electrophoretic technique has been employed for the study ofcomplexes in solution. Here, binary complexes of Mn(II), Fe(II), Co(ll)and Ni(II) formed with m-chlorobenzoic acid and nitrilo triacetic acid(NTA) have been studied along with their ternary complexes formed withthe same ligands used as primary and secondary respectively at fixed pH8.5 maintaining the temperature constant at 35°C and the ionic strength of10-1 M throughout the investigation. The evidence for the formation of1 : 1 complexes of the bivalent metals with m-chlorobenzoic acid wasfound. The stability constants of mixed ligand complexes of the abovemetals formed with m-chlorobenzoic acid and NTA have been found to be7.68, 7.78, 7.86 and 7.93 respectively.